Sistem Pakar Troubleshooting Kerusakan Hardware Laptop Dengan Metode Backward Chaining Berbasis Android - henry chrystianto; Idi Sumardi (Jurnal Ilmiah Infrastruktur Teknologi Informasi, 2021)
Laptop is a very helpful device for human work. Almost all fields use laptops to complete human work. Expert system technology that serves as a substitute for someone who is an expert in their field. Expert systems arise because of problems in a specific specific field, where users want a solution to the problem solved by approaching expert ways in solving problems. There are several methods in expert systems. This study will discuss the Expert System for Troubleshooting Hardware Damage on Laptops, and the inference method used is Backward chaining. Tracking is based on data or facts and then leads to conclusions in the form of conclusions about symptoms of laptop damage or problems that attack the laptop. The system that has been built is tested by comparing the suitability of the system output with the results of expert diagnoses. The test results from 15 case data obtained an accuracy rate of 86.6%. With these accuracy results, it shows that the system is able to help the role of experts